Perancangan Penstock (Pipa Pesat) Untuk Pembangkit Listrik Tenaga Mikrohidro (PLTMH) di Banjar Dinas Mekarsari, Desa Panji, Kecamatan Sukasada, Kabupaten Buleleng - Widiana, I Nengah; Giriantari, Ida Ayu Dwi; Setiawan, I Nyoman (Majalah Ilmiah Teknologi Elektro, 2020)
Since 1980, the village department of Mekar Sari, Panji Village has had a Micro Hydro Power Plant (PLTMH). The PLTMH, which has a 10kW generation capacity, is experiencing various problems resulting in unsuitable operation. One of the proposed improvements is the design of the penstock (fast pipe) in accordance with the MHP Banjar Dinas Mekar Sari. The new penstock design produced penstock with a length of 54 meters, a penstock diameter of 0.8272 meters and a penstock thickness of 0.002 meters. The flow velocity at the penstock after the new design is 2.7088 m / s, and the net head is 16 meters. This improvement is intended to take full advantage of the height of the river flow, so that the maximum flow rate can be generated and then used to rotate the turbine.